Network Activeoncokids – Centralized Physical Activity Counseling for Children, adolescents, and Young Adults Across German-Speaking Countries Throughout All Oncological Treatment Phases - Gauß, Gabriele; Kesting, Sabine; Boos, Joachim; Reinhardt, Dirk; Götte, Miriam (Klinische Pädiatrie, 2024)
Reaching age-appropriate physical activity levels is a significant challenge for many children, adolescents, and young adults (CAYAs) with and following an oncological disease. Many CAYAs require support in addressing physical activity-specific questions and need assistance in accessing sports and exercise offers in their local area. Since many clinics cannot provide such time-intensive counseling, the nationwide operating network ActiveOncoKids (NAOK), funded by the German Cancer Aid, offers individualized support to participate in physical activity (PA). This paper describes the NAOK-Physical-Activity-Counseling (-PAC) concept and evaluates the initial 200 consultations, focusing on recruitment, objectives, and oncology-specific parameters. Ultimately, dimensions of barriers and facilitators and intervention options are discussed.
Keywords: physical activity; counselling; childhood cancer; exercise; re-integration; health behavior